A passive series, active shunt filter for high power applications. - Al-Zamil, A.M (IEEE Transactions on power electronics)
This paper presents a hybrid series passive/shunt active power filter system for high power nonlinear loads. This work is motivated by the fact that the ability of a converter to perform effectively as an active filter is limited by the power and the frequency distribution of the distortion for which it must compensate. This system is comprised of a three-phase shunt active filter and series AC line smoothing reactance installed in front of the target load. The proposed system significantly reduces the required shunt active filter bandwidth. The space-vector pulse width modulation (PWM) controller is based on a dead-beat control model. It is implemented digitally using a single 16-bit microcontroller. This controller requires only the supply current to be monitored, an approach different from conventional methods. The paper provides background on the operation of the filter, the details of the power circuit, the details of the control design, representative waveforms, and spectral performance for a filter which supports a 15 kVA phase controlled rectifier load. Experimental data indicate that the active filter typically consumes 2% or less of the average load power, suggesting that a parallel filter is an efficient compensation approach. The spectral performance shows that the active filter brings the system into compliance with IEEE519-1992 up to the 33rd harmonic for an AC line smoothing reactance of 0.13 p.u